The awakening of Le'Andria Johnson [compact disc]. - Johnson, Le'Andria, 1983- (Music World Music : Distributed by Fontana, 2011)
BET's 2010 Sunday Best Season 3 winner, Le'Andria Johnson, captured viewers' attention. Her debut CD features her lead track, Jesus. She is an anointed worship and praise leader and a talented, self-taught musician.